Does Climate Warming Favour Early Season Species? - Chu, Xiuli; Man, Rongzhou; Zhang, Haicheng; Yuan, Wenping; Tao, Jing; Dang, Qing-Lai (Frontiers in Plant Science, 2021)
Plant species that start early in spring are generally more responsive to rising temperatures, raising concerns that climate warming may favor early season species and result in altered interspecific interactions and community structure and composition. This hypothesis is based on changes in spring phenology and therefore active growing season length, which would not be indicative of possible changes in growth as would changes in cumulative forcing temperatures (growing degree days/hours) in the Northern Hemisphere. In this study we analyzed the effects of a moderate climate warming (2 °C warmer than the 1981–2010 baseline) on the leaf-out of hypothetical species without chilling restriction and actual plant species with different chilling and forcing requirements in different parts of the globe. In both cases, early season species had larger phenological shifts due to low leaf-out temperatures, but accumulated fewer forcing gains (changes in cumulative forcing temperatures by warming) from those shifts because of their early spring phenology. Leaf-out time was closely associated with leaf-out temperatures and therefore plant phenological responses to climate warming. All plant species would be equally affected by climate warming in terms of total forcing gains added from higher temperatures when forcing gains occurring between early and late season species are included. Our findings will improve the understanding of possible mechanisms and consequences of differential responses in plant phenology to climate warming.